Learning management systems with emphasis on the Moodle at UniSA - Ghosh, Anusua; Nafalski, Andrew; Nedic, Zorica; Wibawa, Aji Prasetya (Association for Scientific Computing Electrical and Engineering, 2019)
With recent advances in technology and the Internet, the concept of teaching and learning have evolved significantly. Conventional face-to-face teaching is becoming a thing of the past as knowledge is everywhere and accessible from anywhere. Thus, a shift to e-learning is gaining momentum. Educational institute, companies, individuals and training organizations are embracing new technology and creating a shared online platform to facilitate learning, referred to as the Learning Management Systems (LMS). LMS are software that provide an online portal to collaborate in teaching and learning seamlessly, making it more productive and engaging. This paper aims to review the top ten LMSs both cloud based and open source with regards to their compatibility, usefulness, security, accessibility, scalability, stability/reliability and de-sign in general with emphasis on the recent development of the Moodle and NetLab at University of South Australia (UniSA). The open source online learning platform Moodle is adopted by UniSA to provide educators a space for collaborative learning using the optimized tools to create activities. Moreover, the Netlab online remote laboratory developed at UniSA, provides a platform for academic staff for teaching and demonstrations during lectures and for students to conduct practical experiments remotely on real laboratory equipment.